Tectonics of the Qinling (Central China): tectonostratigraphy, geochronology, and deformation history - Ratschbacher, Lothar; Hacker, Bradley R.; Calvert, Andrew; Webb, Laura E.; Grimmer, Jens Carsten; McWilliams, Michael O.; Ireland, Trevor; Dong, Shuwen; Hu, Jianmin (Tectonophysics, 2003)
The Qinling orogen preserves a record of late mid-Proterozoic to Cenozoic tectonism in central China. High-pressure metamorphism and ophiolite emplacement (Songshugou ophiolite) assembled the Yangtze craton, including the lower Qinling unit, into Rodinia during the ∼1.0 Ga Grenvillian orogeny. The lower Qinling unit then rifted from the Yangtze craton at ∼0.7 Ga. Subsequent intra-oceanic arc formation at ∼470-490 Ma was followed by accretion of the lower Qinling unit first to the intra-oceanic arc and then to the Sino-Korea craton. Subduction then imprinted a ∼400 Ma Andean-type magmatic arc onto all units north of the northern Liuling unit. Oblique subduction created Silurian-Devonian WNW-trending, sinistral transpressive wrench zones (e.g., Lo-Nan, Shang-Dan), and Late Permian-Early Triassic subduction reactivated them in dextral transpression (Lo-Nan, Shang-Xiang, Shang-Dan) and subducted the northern edge of the Yangtze craton. Exhumation of the cratonal edge formed the Wudang metamorphic core complex during dominantly pure shear crustal extension at ∼230-235 Ma. Post-collisional south-directed shortening continued through the Early Jurassic. Cretaceous reactivation of the Qinling orogen started with NW-SE sinistral transtension, coeval with large-scale Early Cretaceous crustal extension and sinistral transtension in the northern Dabie Shan; it presumably resulted from the combined effects of the Siberia-Mongolia—Sino-Korean and Lhasa-West Burma—Qiangtang-Indochina collisions and Pacific subduction. Regional dextral wrenching was active within a NE-SW extensional regime between ∼60 and 100 Ma. An Early Cretaceous Andean-type continental magmatic arc, with widespread Early Cretaceous magmatism and back-arc extension, was overprinted by shortening related to the collision of Yangtze-Indochina Block with the West Philippines Block. Strike-slip and normal faults associated with Eocene half-graben basins record Paleogene NNE-SSW contraction and WNW-ESE extension. The Neogene(?) is characterized by normal faults and NNE-trending sub-horizontal extension. Pleistocene(?)-Quaternary NW-SE extension and NE-SW contraction comprises sinistral strike-slip faults and is part of the NW-SE extension imposed across eastern Asia by the India-Asia collision.
Gesehen am 23.09.2020